EFFECTS OF FEEDBACK NN SKILLS DURING CARDIOPULMONAL REANIMATION TRAINING - Ciekurs, Rafaels; Balmaks, Reinis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Sudden cardiac arrest is one of the main causes of death in Europe. Early initiation and qualitative performance of cardiopulmonary resuscitation can reduce mortality. In order to perform cardio-pulmonary resuscitation of appropriate quality, theoretical and practical knowledge is needed which can be improved by clinical simulation. The aim of the study was to find out the effect of feedback on participants' skills during cardiopulmonary resuscitation training. Hypothesis - feedback improves participants' skills during cardiopulmonary resuscitation training. Research Method - randomized controlled simulation study. Research instruments - observation protocol, questionnaire. A total of 32 employees of State Emergency Medical Service (medical practitioners) participated in the study. The hypothesis was confirmed - feedback improves participants' skills during cardiopulmonary resuscitation training. The total evaluation of cardiopulmonary resuscitation in the intervention group, which performed the cardiopulmonary resuscitation scenario with the feedback function is higher (92,13%) compared to the control group (77%). Most of the participants in the intervention group fully agree that the use of feedback function during training improves the overall cardiopulmonary resuscitation skills. The results of the study indicate that the development of cardiopulmonary resuscitation training programs for medical students and practitioners requires the inclusion of practical activities with clinical simulations with feedback.